(untitled) - Considine, Glenn D. (Hoboken, N.J., 2005)
A previous edition of this work is cited in Books for College Libraries, 3d ed. and Guide to Reference Books as Van Nostrand Reinhold Encyclopedia of Chemistry, and in Walford under the present title. Encompassing a wide range of topics now pertinent to chemistry, 1,350 entries are new to this edition in the subjects of nanotechnology, fuel cell technology, green chemistry, forensic chemistry, supramolecular chemistry, combinatorial chemistry, and materials chemistry. The other entries have been revised and updated, the subject index has been expanded, and more biographies have been added. The editors have requested particular emphasis from their writers on several factors, including advanced processes, strategic raw materials, chemistry of metals, energy sources and conversion, wastes and pollution, analytical instrumentation, growing use of food chemicals, structure of matter, new and improved materials, plant chemistry, and biochemistry and biotechnology. The entries are written with both student and the specialist in mind, and include basic description and history as well as advanced concepts and applications. The entries are signed and include a brief list of additional reading. Some also include lists of web references.
Keywords: Chemistry